Pemberdayaan Masyarakat Melalui Pendidikan, Optimalisasi Sumber Daya dan Alam di Desa Mayang Pongkai Kecamatan Kampar Kiri Tengah - Raihana; Inriyemi Delfita; Hera Marina; Bramudia Sakra Putra; Firsahabat Putra Laia; Radika Frisilia; Zahra Indah Fahrani; M.Guntur Dwi Nicko; Muhammad Dimas; Gylang Rahmadi; Assadul Muhammad (LPPM UMRI, 2023)
Real Work Lecture (KKN) is an intracurricular form which is an implementation of the Tridharma of Higher Education to provide students with work and learning experiences in community empowerment. Real work lecture activities are a golden opportunity for students who are smart, critical, innovative and creative in findingthe right solutions, formulas and strategies for various problems of business units.The placement of KKN student locations is mostly directed at villages that havesuperior potential but still lack community skills in managing their natural products.This is a challenge for the group of real lecture participants to change the existingsuperior potential of the village with economic value through a communityempowerment work program that will be directly assisted by practitioners and theacademic community from the University of Muhammadiyah Riau. The communityservice method carried out by KKN students is through KKN debriefing,entrepreneurship counseling and mentoring, educational seminars and socializationof Covid-19 and evaluation of KKN activities. The target in this activity is thecommunity around the KKN location consisting of housewives, personal microbusiness owners and children